Analysis of changes in climatological condition: a perspective from Barguna district of Bangladesh - Kormoker, Tapos; Proshad, Ram; Mahmud Khan, Mohammed; Chandra Saha, Bidhan (International Journal of Advanced Geosciences, 2017)
This study investigated the long-term changes in climatological condition, such as temperature, rainfall, humidity, storms, and tidal surge and flooding in Barguna district of Bangladesh. The BMD (Bangladesh Meteorological Department) data were used for temperature, rainfall, and humidity. The data for storms have been collected from secondary sources i.e. various journals, website and various records. This study applied the time series statistical test to examine the long-term changes in climatological condition, such as temperatures (1970-2015), rainfall (1975-2013), humidity (1975-2013), and storms (1987-2007). A parametric technique of trend analysis was used in this study for its inclusive use and simplicity. Data screening and filling missing values were also done before the analyses. The analyses of measured temperature indices that the annual average maximum and minimum mean temperature has increased 1.16Â°C and 0.56Â°C respectively at the end of 2015 since 1982 indicating that the weather has been becoming hotter. The analysis of the last 30 years rainfall data of Barguna was compared with national total annual rainfall and no significant change observed. The number of wetter days has been increasing over the time and more rainfall has been happening within small time. There is also a significant change in relative humidity. A total of thirty-five depressions, storms and cyclones hit Barguna district during the last 130 years among which hard hit severe cyclones have occurred in 1935, 1965, 1970 and the most recent cyclone SIDR in 2007 was notable. The study found that storm surge level and surge induced coastal flooding reached from the outfall of Baleshwar River up to 50 km upstream at Morrelganj with high surge level. Therefore, this study will provide a condensed view in further studies in advanced statistical modeling in combination with future scenario analysis for micro and macro scale climate variable changes in Bangladesh.